"To Own or Not to Own?" A Study on the Determinants and Consequences of Alternative Intellectual Property Rights Arrangements in Crowdsourcing for Innovation Contests. Issue 6 (23rd September 2018) - Mazzola, Erica; Acur, Nuran; Piazza, Mariangela; Perrone, Giovanni
Abstract : Firms are increasingly engaging in crowdsourcing for innovation to access new knowledge beyond their boundaries; however, scholars are no closer to understanding what guides seeker firms in deciding the level at which to acquire rights from solvers and the effect that this decision has on the performance of crowdsourcing contests. Integrating property rights theory and the problem‐solving perspective while leveraging exploratory interviews and observations, we build a theoretical framework to examine how specific attributes of the technical problem broadcast by firms affect the seekers' choice between alternative intellectual property rights (IPR) arrangements that call for acquiring or licensing‐in IPR from external solvers (i.e., with high and low degrees of ownership, respectively). Each technical problem differs in the knowledge required to be solved as well as in the stage of development of the innovation process and seeker firms pay great attention to such characteristics when deciding about the IPR arrangement they choose for their contests. In addition, we analyze how this choice between acquiring and licensing‐in IPR, in turn, influences the performance of the contest. We empirically test our hypotheses analyzing a unique dataset of 729 challenges broadcast on the InnoCentive platform from 2010 to 2016. Our results indicate that challenges related to technical problems in later stages of the innovation process are positively related to the seekers' preference toward IPR arrangements with a high level of ownership, while technical problems involving a higher number of knowledge domains are not. Moreover, we found that IPR arrangements with a high level of ownership negatively affect solvers' participation and that IPR arrangement play a mediating role between the attributes of the technical problem and the solvers' self‐selection process. Our paper contributes to the open innovation and crowdsourcing literature and provides practical implications for both managers and contest organizers.